Compliance of selected stingless bee honey in Kelantan according to Malaysian Standard (MS) 2683:2017 - Noor Hafizoh Saidan,; Norsyahira Roslan,; Nur Rahiiqin Maktuum Baharuddin,; Mohd Shahrul Ridzuan Hamil,; Kumara Thevan Krishnan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
In Malaysia, commercial stingless bee honey is in demand due to its nutritional and healing properties, especially in the cosmetic, food and beverage and pharmaceutical industry. However, up to date, these honey products from various districts of Kelantan were not subjected to compliance according to the specification of the Malaysian Standard (MS) 2683:2017. Thus, the objective of the current study was to determine the compliance of selected stingless bee honey (SBH) in Kelantan based upon physicochemical properties and microbiological analysis following MS 2683:2017 specifications. Physicochemical analysis of commercial stingless be honey shows the value of moisture, ash, hydroxymethylfurfural (HMF) and pH were in the range of 27.05 ± 1.39 to 32.61 ± 2.79 %, 0.08 ± 0.01 to 0.14 ± 0.01 g, 8.78 ± 0.92 to 218.66 ± 0.70 mg/kg and 2.34 ± 0.01 to 3.22 ± 0.02, respectively. There was an absence of total coliform in all samples. In summary, all samples of stingless bee honey complied with MS 2683:2017 specification for physicochemical properties and microbial contaminant limits of total plate count (TPC) and total coliform. However, for the microbial contaminant limit of yeast and mold, only sample 6 was contaminated.